DUKUNGAN KELUARGA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA LANSIA DIDESA OLLOT SATU KECAMATANBOLANGITANG BARAT KABUPATEN BOLAANG MONGONDOWUTARA - Rona Ferbriyona; Andi Nuraina Sudirman; Meyvita Dewi Humokor (Universitas Muhammadiyah Gorontalo, 2020)
Elderly is someone over 60 years old that has decreased function and structure of the body's organs. In Clean and Healthy Behavior of elderly is need family support. The objective of research was to determine The Relationship of Family Support with Clean and Healthy Behavior in Elderly at Ollot Satu Village. Type of research used quantitative with analytic survey design and cross sectional approach, sampling technique used certain considerations or criteria using a questionnaire on 49 respondents. The samples determinate used Purposive sampling.data analysis used Spearman Rho test. The result showed family support with good category is 42 respondents (85.7%) and in less category is 7 respondents (14.3%), Clean and Healthy Behavior with good category is 41 respondents (83.7%) and in less category 8 reponden (16.3%).